EST-derived polymorphic microsatellites from cultivated strawberry (Fragaria × ananassa) are useful for diversity studies and varietal identification among Fragaria species - Gil-Ariza, David Jesús; Amaya, Iraida; Botella-Mesa, Miguel Ángel; Muñoz-Blanco, Juan; Caballero, José Luis; López Aranda, José Manuel; Valpuesta-Fernández, Victoriano; Sánchez-Sevilla, José F. (Wiley, 2006)
Microsatellite or simple sequence repeat markers derived from expressed sequence tags (ESTs) provide genetic markers within potentially functional genes, which could be very useful for breeding programs. To date, the development of microsatellite markers in the genus Fragaria has focused mainly on Fragaria vesca. However, most of the interests of breeding programs relate to specific characteristics of cultivated strawberry. Here, we describe a set of 10 EST-derived microsatellites from Fragaria × ananassa. These markers showed high levels of polymorphism within strawberry cultivars and among different Fragaria species, indicating their potential for genetic studies not only on strawberry but also in other species within the genus.
Keywords: Fresas - Variedades - Aspectos genéticos; Fragaria; Cultivar identification; Expressed sequence tags; Simple sequence repeats